The Influence of Leadership Style and Work Discipline on Employee Performance At PT. Bank Central Asia Asia Branch Medan - Fenny Cendryani (LPPM STIE EKA PRASETYA, 2022)
This study aims to determine the effect of leadership style and work discipline on employee performance. The population in this study were all employees at PT. Bank Central Asia KCU Asia Medan, totaling 50 employees. The sample is a subset of the population, consisting of all members of the population. The analysis used in this study using multiple linear regression analysis. The results showed that leadership style and work discipline together had a positive and significant effect on employee performance at PT. Bank Central Asia KCU Asia Medan